Bilingual couples talk : the discursive construction of hybridity - Piller, Ingrid, 1967- (Studies in bilingualism, 2002)
This sociolinguistic study of the linguistic practices of bilingual couples describes the conditions, processes and results of private language contact. It is based on a unique corpus of more than 20 hours of private conversations between partners in bilingual marriages. Adding to its breadth of coverage, these private conversations are supplemented with larger public discourses about international couplehood. The volume thus offers a corpus-driven investigation of the ways in which ideologies of gender, nationality and immigration mediate linguistic performances in private cross-cultural comm.